Legal Language as an Instrument for Describing Social Reality. Searching for Innovative Narrations - Kohtamäki, Natalia (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
How we function in social reality is determined by various types of cognitive schemas. These concern people, social events and other phenomena. According to the concept offered by various postpositivist currents, including postmodernism, poststructuralism and critical theory, such schemata cannot be objective. The most important element of postmodern considerations is the discovery of the arbitrary nature of modernity. This means rejecting the Enlightenment belief in progress. Innovation, understood as modernity resulting from human reason, is illusory in the postmodern perspective. Innovation consists precisely in a rejection of the myth of the existence of some absolute, objective truths that constitute the social order. The world is textual, made up of many alternative narratives. Definitions, including legal definitions, are socially constructed. They arise from specific social conditions, at a particular stage of development of a particular group. The assumption made by postmodernists is that language, including professional language – such as the language of law or legal language – is neither neutral nor transparent. The innovative power of this language lies in its use of narratives that influence the functioning of social groups of varying degrees of complexity. It is therefore necessary, adopting a postmodern interpretation, to look at the text of legal language in a similar way as we look at other texts. That is, to see in the narrativity of this language structural similarities with other texts that constitute social reality.